Auxin regulation involved in gynoecium morphogenesis of papaya flowers. Issue 1 (1st November 2019) - Zhou, Ping; Fatima, Mahpara; Ma, Xinyi; Liu, Juan; Ming, Ray
Abstract: The morphogenesis of gynoecium is crucial for propagation and productivity of fruit crops. For trioecious papaya ( Carica papaya ), highly differentiated morphology of gynoecium in flowers of different sex types is controlled by gene networks and influenced by environmental factors, but the regulatory mechanism in gynoecium morphogenesis is unclear. Gynodioecious and dioecious papaya varieties were used for analysis of differentially expressed genes followed by experiments using auxin and an auxin transporter inhibitor. We first compared differential gene expression in functional and rudimentary gynoecium at early stage of their development and detected significant difference in phytohormone modulating and transduction processes, particularly auxin. Enhanced auxin signal transduction in rudimentary gynoecium was observed. To determine the role auxin plays in the papaya gynoecium, auxin transport inhibitor (N-1-Naphthylphthalamic acid, NPA) and synthetic auxin analogs with different concentrations gradient were sprayed to the trunk apex of male and female plants of dioecious papaya. Weakening of auxin transport by 10 mg/L NPA treatment resulted in female fertility restoration in male flowers, while female flowers did not show changes. NPA treatment with higher concentration (30 and 50 mg/L) caused deformed flowers in both male and female plants. We hypothesize that the occurrence of rudimentary gynoecium patterning might associate with auxin homeostasis alteration. Proper auxin concentration and auxin homeostasis might be crucial for functional gynoecium morphogenesis in papaya flowers. These results will lead to further investigation on the auxin homeostasis and gynoecium morphogenesis in papaya.